2015
DOI: 10.18632/oncotarget.5403
|View full text |Cite
|
Sign up to set email alerts
|

Design of a peptidic inhibitor that targets the dimer interface of a prototypic galectin

Abstract: Galectins are small soluble lectins that bind β-galactosides via their carbohydrate recognition domain (CRD). Their ability to dimerize is critical for the crosslinking of glycoprotein receptors and subsequent cellular signaling. This is particularly important in their immunomodulatory role via the induction of T-cell apoptosis. Because galectins play a central role in many pathologies, including cancer, they represent valuable therapeutic targets. At present, most inhibitors have been directed towards the CRD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 51 publications
(43 reference statements)
0
26
0
Order By: Relevance
“…These findings are of great importance in the design of gal-7 inhibitors for the treatment of various diseases where gal-7 plays a central role, most notably in cancer [ 6 , 7 , 9 ]. These findings suggest that targeting extracellular gal-7 using either CRD-specific inhibitors [ 14 ] or dimer-disrupting peptides (DIPs) [ 13 ] may be more efficient than expected for targeting intracellular gal-7-mediated interactions. Furthermore, our results showing that extracellular gal-7 induces de novo lgals7 gene activation and our approach using FITC-tagged recombinant gal-7 to follow the fate of extracellular gal-7 inside the cells provide new and original in vitro model systems to investigate the inhibitory activity of these gal-7-specific inhibitors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are of great importance in the design of gal-7 inhibitors for the treatment of various diseases where gal-7 plays a central role, most notably in cancer [ 6 , 7 , 9 ]. These findings suggest that targeting extracellular gal-7 using either CRD-specific inhibitors [ 14 ] or dimer-disrupting peptides (DIPs) [ 13 ] may be more efficient than expected for targeting intracellular gal-7-mediated interactions. Furthermore, our results showing that extracellular gal-7 induces de novo lgals7 gene activation and our approach using FITC-tagged recombinant gal-7 to follow the fate of extracellular gal-7 inside the cells provide new and original in vitro model systems to investigate the inhibitory activity of these gal-7-specific inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Production of human recombinant gal-7 was carried out as described using a pET-22b(+) plasmid encoding a synthetic, codon-optimized cDNA [ 13 ]. In some experiments, recombinant gal-7 was labeled with fluorescein isothiocyanate (FITC) as described [ 13 ]. FITC-labeled gal-7 was purified using a PD-10 Sepharose column (GE healthcare) and eluted with PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Serum galectin-7 concentration is a promising prospective biomarker for predicting subsequent miscarriage or the development of preeclampsia in pregnancy (15,23). Galectin-7 may also have potential as a therapeutic target to treat EC, and inhibitors are currently being developed (38) and could be tested in mouse models of EC. Overall, the present study has identified galectin-7 as a novel mediator of EC progression.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, extracellular Gal7 induced T-cell apoptosis whereas intracellularly this lectin controlled proliferation and differentiation of keratinocytes through mechanisms involving the JNK1, miR-203 and p63 signaling pathways (120)(121)(122). Enforced expression of Gal7 in cancer cells controlled several molecular networks involved in metabolism, survival and immunity (123).…”
Section: H Other Galectinsmentioning
confidence: 99%